Modified porous powder and preparation method thereof, battery diaphragm and battery
By introducing a modified additive containing carboxylate on the surface of the porous powder particles, a modified porous powder was prepared, which solved the problem of manganese ions being transferred to the negative electrode in the lithium battery, and achieved effective adsorption of manganese ions and improved battery performance.
Patent Information
- Application Number
- CN202510030478.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-25
AI Technical Summary
When using lithium batteries containing a positive electrode active material with manganese, manganese ions may dissolve from the positive electrode during charging/discharging and move to the negative electrode, resulting in uneven film formation and deteriorating the capacity of the electrochemical device. In the prior art, sulfonic acid groups are used to adsorb manganese ions, but may react with lithium in the positive electrode material, resulting in structural damage and capacity loss.
A modified porous powder is provided, which includes porous powder particles and a carboxylate-containing modification additive loaded on the surface of the porous powder particles. The loading of the modification additive is 1-10 wt%, which can effectively adsorb manganese ions and prevent manganese from moving to the negative electrode, while not reacting with the positive electrode material.
By introducing carboxylic acid groups, the modified porous powder can effectively adsorb manganese ions, prevent them from being transferred to the negative electrode, improve the stability and capacity of the battery, and avoid reaction with the positive electrode material, further improve the battery performance.
Smart Images

Figure BDA0005233997900000131 
Figure BDA0005233997900000141
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery separators, and in particular to a modified porous powder and a preparation method thereof, a battery separator and a battery. Background Art
[0002] Batteries convert chemical energy into electrical energy using electrochemical reactions. Lithium batteries, in particular, are widely used due to their high energy density and voltage, long cycle life, and ability to be used in a variety of fields.
[0003] Lithium-ion batteries generally include a positive electrode, a negative electrode, an electrolyte, and a separator between the positive electrode and the negative electrode. Among them, the main function of the positive electrode active material is to provide lithium ions, which determines the energy density of the battery. The positive electrode active material can contain lithium and various metal elements or transition metal elements, such as nickel can improve the capacity of the battery, cobalt can improve the capacity and cycle stability of the battery, and aluminum can improve the output characteristics of the battery.
[0004] However, since nickel has low thermal stability and nickel and cobalt are expensive, many positive electrode active materials require the addition of manganese to improve battery stability and reduce battery costs.
[0005] However, when using a lithium battery containing a manganese-containing positive electrode active material, manganese ions may be dissolved from the positive electrode during the charge / discharge process. The dissolved manganese ions can move to the negative electrode, precipitate on the surface of the negative electrode as impurities containing manganese, and form an uneven film, thereby causing the capacity of the electrochemical device to deteriorate. CN 117981159 A discloses a separator for an electrochemical device comprising a lithium-manganese-based active material, which has a sulfonic acid group introduced on the surface of the second inorganic particle, which can produce an adsorption effect of manganese ions. However, the sulfonic acid group carries sulfur, which may react with lithium in the positive electrode material to form an unstable compound, resulting in structural damage and capacity loss of the positive electrode material, and the patent disclosure process is relatively complicated.
[0006] Therefore, it is necessary to provide a new particle that can be used for a separator, which can not only adsorb manganese ions, but also will not react with elements such as lithium, and can improve the performance of lithium batteries.
[0007] In view of this, the present invention is proposed. Summary of the invention
[0008] The object of the present invention is to provide a modified porous powder and a preparation method thereof, a battery separator and a battery. The embodiment of the present invention provides a modified porous powder, which can be used to prepare a battery separator, can effectively adsorb manganese in the battery, prevent manganese from moving to the negative electrode, and will not react with the positive electrode material, thereby improving the performance of the battery.
[0009] The present invention is achieved in that:
[0010] In a first aspect, the present invention provides a modified porous powder, which comprises porous powder particles and a carboxylate-containing modification aid loaded on the surface of the porous powder particles;
[0011] Wherein, the loading amount of the modification aid is 1-10wt%.
[0012] In an optional embodiment, the mass ratio of the porous powder particles to the modification aid is (10:1)-(100:1);
[0013] Preferably, the particle size of the modified porous powder is 0.1-2 μm.
[0014] In an optional embodiment, the porous powder particles are selected from any one of porous silica particles, porous titanium dioxide particles, porous zirconium oxide particles and porous aluminum oxide particles; preferably porous aluminum oxide particles;
[0015] Preferably, the pore volume of the porous powder particles is 0.01 to 0.1 cm 3 / g;
[0016] Preferably, the pore size of the porous powder particles is 3 to 50 nm;
[0017] Preferably, the particle size of the porous powder particles is 0.1-2 μm;
[0018] Preferably, the modification aid is selected from raw materials containing carboxylate groups and being easily soluble in water;
[0019] Preferably, the modification aid is selected from at least one of citric acid, succinic acid, polyacrylic acid, formic acid, acetic acid, propionic acid, butyric acid and tartaric acid.
[0020] In a second aspect, the present invention provides a method for preparing the modified porous powder according to the aforementioned embodiment, comprising:
[0021] The porous powder particles are mixed with the modification aid to carry out a hydrothermal reaction.
[0022] In an optional embodiment, the conditions of the hydrothermal reaction include: a temperature of 90-170° C. and a time of 4 h-48 h.
[0023] In an optional embodiment, the step of preparing the porous powder particles includes: performing a first hydrothermal reaction on a hydroxide to form a first metal reactant;
[0024] Then, the first metal reactant is calcined to form porous powder particles.
[0025] In an optional embodiment, the method comprises: mixing the hydroxide and the doping aid to perform a first hydrothermal reaction to form a first metal reactant;
[0026] Preferably, the amount of the doping aid added is 0.01-1wt% of the amount of the hydroxide added;
[0027] Preferably, the doping aid is selected from ammonium substances, preferably triquaternary ammonium or trimethylammonium.
[0028] In an optional embodiment, the conditions of the first hydrothermal reaction include: a temperature of 120-240° C. and a time of 4-48 h;
[0029] Preferably, the particle size of the first metal reactant is 0.1-2 μm;
[0030] Preferably, the crystal water content in the first metal reactant is 17-30%;
[0031] Preferably, the first metal reactant is M x O y nH2O, wherein 1≤n≤2, M represents the metal in the porous powder particles, x is 1-2, and y is any integer between 1-3;
[0032] Preferably, the method comprises: spray drying the first metal reactant before calcining the first metal reactant;
[0033] Preferably, the calcination conditions include: a temperature of 500-1200° C., a time of 0.5-10 h, and a calcination heating rate of 1-10° C. / min.
[0034] In a third aspect, the present invention provides a battery separator, which includes a film substrate and a coating disposed on the film substrate, wherein the coating is prepared by the modified porous powder described in the aforementioned embodiment.
[0035] In a fourth aspect, the present invention provides a battery, comprising the battery separator described in the aforementioned embodiment.
[0036] The present invention has the following beneficial effects: an embodiment of the present invention provides a modified porous powder, which introduces carboxylic acid groups on the surface of the porous powder particles, thereby being able to adsorb manganese ions and prevent the manganese ions from being transferred to the negative electrode. At the same time, the modified porous powder will not react with the positive electrode, and can further improve the performance of the battery. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0038] In a first aspect, the present invention provides a modified porous powder, which includes porous powder particles and a carboxylate-containing modification aid loaded on the surface of the porous powder particles. The carboxylate-containing modification aid is loaded on the surface of the porous powder particles, which means that the carboxylate is also loaded on the surface of the porous powder particles. The surface refers to the surface of the porous powder particles where no pores are formed and the inner surface of the pores.
[0039] Carboxylic acid groups are introduced on the surface of porous powder particles. The carboxylic acid groups can fully absorb manganese ions, prevent manganese ions from transferring to the negative electrode of the battery, and improve the stability and capacity of the battery. The modified porous powder will not react with the positive electrode active material, further improving the structure and capacity of the positive electrode material and the performance of the battery. At the same time, the modified porous powder also has a porous structure, which improves the liquid retention and ionic conductivity of the diaphragm, further improving the performance of the battery.
[0040] Further, the loading amount of the modifying agent is 1-10wt%, such as 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% and 10wt%, any value between 1-10wt% or a range between any two values. It is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0041] If the loading amount of the modification aid is lower than 1wt%, the modified porous powder cannot achieve the effect of adsorbing manganese ions. If the loading amount of the modification aid is higher than 10%, the adsorption effect cannot be further improved, and it will lead to strong bonding between particles, affecting the lithium ion transmission effect.
[0042] The loading amount of the modification aid is calculated as follows: (the mass of the modification aid added during the reaction - the mass of the modification aid remaining after the reaction) / the mass of the modification aid added during the reaction. The loading amount of the modification aid is also the loading amount of the carboxylic acid group.
[0043] Furthermore, the mass ratio of the porous powder particles to the modifying agent is (10:1)-(100:1); for example, any value between (10:1)-(100:1) such as 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1 and 100:1. It is not limited to the listed values, and other values not listed within the numerical range are also applicable. That is to say, the amount of the modifying agent added is 1-10wt% of the amount of the porous powder particles added.
[0044] Furthermore, the particle size of the modified porous powder is 0.1-2 μm, which can realize the setting of a thinner coating of the diaphragm. At the same time, the porous structure of the modified porous powder improves the liquid retention and ion conductivity of the diaphragm. The modified porous powder is also loaded with a modification additive, which can remove manganese ions in lithium-ion batteries and improve the reliability and safety of lithium-ion batteries.
[0045] The porous powder particles are selected from any one of porous silica particles, porous titania particles, porous zirconia particles and porous alumina particles; preferably porous alumina particles.
[0046] The embodiments of the present invention only use porous alumina particles as an example to illustrate the technical solution, but it is understandable that porous silica particles, porous titanium dioxide particles, and porous zirconium oxide particles can also achieve the same or similar technical effects.
[0047] Among them, the pore volume of porous powder particles is 0.01-0.1cm 3 / g; for example 0.01cm 3 / g, 0.05cm 3 / g, 0.1cm 3 / g etc. 0.01-0.1cm 3 / g. However, it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0048] The particle size of the porous powder particles is 0.1-2 μm, for example, 0.1 μm, 0.2 μm, 0.3 μm, 0.5 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm and 2 μm, etc., any value between 0.1-2 μm. However, it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0049] The introduction of carboxylic acid groups on the surface of porous powder particles has little effect on the particle size of the porous powder particles. Basically, the particle size of the porous powder particles is not much different from that of the modified porous powder.
[0050] When the average particle size of the porous powder particles is less than 0.1 μm, an additional polymer binder is required for bonding between the inorganic particles, which is disadvantageous in terms of resistance. When the average particle size of the porous powder particles exceeds 2 μm, the uniformity of the coating surface is reduced, and the separator and the electrode may be damaged by the particles protruding after coating during lamination, resulting in a short circuit.
[0051] The pore size of the porous powder particles is 3-50 nm, for example, 3 nm, 4 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm, etc., any value between 3-50 nm. However, it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0052] If the pore diameter of the porous powder particles is less than 3 nm, the pore size is too small, and macroporous inorganic particles having an average pore diameter exceeding 50 nm have a small pore volume, thus making it difficult to ensure adsorption performance for manganese ions by introducing carboxyl groups.
[0053] Furthermore, the modification aid is selected from raw materials containing carboxylate groups and being easily soluble in water; for example, including but not limited to at least one of citric acid, succinic acid, polyacrylic acid, formic acid, acetic acid, propionic acid, butyric acid and tartaric acid.
[0054] The modified additive is easily soluble in water, and can then be better dispersed in the aqueous formula, becoming more uniform after modification, and can be better loaded onto the surface and pores of the porous powder particles during the hydrothermal reaction, retaining the carboxyl groups.
[0055] Specifically, when the modified porous powder is used in a battery, when hydrogen cations are released from the carboxyl groups introduced into the porous powder particles, an attractive force acts between the electron-rich oxygen atoms and the manganese ions, thereby giving the porous powder particles the ability to adsorb manganese ions.
[0056] In a preferred embodiment of the present invention, the modification aid is selected from polyacrylic acid, which is relatively stable and has the functions of a binder and a dispersant, and can improve the dispersibility of the slurry during the pulping process and the adhesion of the coating after coating.
[0057] Furthermore, the preparation method of the modified porous powder is not particularly limited as long as the effect of the embodiment of the present invention is exerted. For example, the hydrothermal method, the solid phase method, the sol-gel method and the seed precipitation method are all possible. From the perspective of easily obtaining a modified porous powder with good manganese removal effect, the embodiment of the present invention is preferably the hydrothermal method.
[0058] Specifically, S1, forming porous powder particles:
[0059] A first hydrothermal reaction is performed on the hydroxide to form a first metal reactant; and then the first metal reactant is calcined to form porous powder particles.
[0060] Specifically, the hydroxide and the doping aid are mixed to perform a first hydrothermal reaction to form a first metal reactant. That is, the hydroxide is dissolved in a solvent, and the doping aid is heated to form a uniform precursor solution, thereby ensuring the formation of a pore structure in the subsequent process. The addition of the doping aid helps to control the pore size and porosity of the final porous powder particles (such as porous alumina) so that it meets the required structural requirements and ensures the porous characteristics of the material.
[0061] Furthermore, the amount of the doping aid added is 0.01-1wt% of the amount of the hydroxide added. For example, any value between 0.01wt%, 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% and 1wt% is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0062] The doping aid is selected from ammonium substances, such as triquaternary ammonium or trimethylammonium.
[0063] For example, the temperature of the first hydrothermal reaction is 120-240° C., such as 120° C., 130° C., 140° C., 150° C., 160° C., 170° C., 180° C., 190° C., 200° C., 210° C., 220° C., 230° C., and 240° C., etc., any value between 120-240° C. However, it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0064] The time of the first hydrothermal reaction is 4-48 hours, for example, any value between 4-48 hours such as 4h, 5h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h and 48h, etc. However, it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0065] The first metal reactant is M x O y·nH2O, wherein 1≤n≤2, M represents the metal in the porous powder particles, x is 1-2, and y is any integer between 1-3. For example, the first alumina reactant has a structural formula of Al2 O3·nH2 O, wherein 1≤n≤2, such as 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 and 2, etc., any value between 1 and 2. However, it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0066] The particle size of the first metal reactant is 0.1-2 μm, such as 0.1 μm, 0.2 μm, 0.3 μm, 0.5 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm and 2 μm, etc., any value between 0.1-2 μm. However, it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0067] The crystal water content in the first metal reaction body is 17-30%.
[0068] The first metal reactant is then spray dried and then calcined to form porous powder particles. During the calcination process, no additional sintering aid and pore-forming agent are required to obtain porous powder particles with a porous structure and different pore volumes and pore diameters.
[0069] In summary, the embodiments of the present invention can obtain a porous structure and porous powder particles (such as porous alumina) by hydrothermal reaction of hydroxide and doping auxiliary agent and calcination process in coordination, so as to meet the needs of the next generation of lithium ion battery separators. If the present invention is not doped with auxiliary agent, it cannot achieve a porous structure, and cannot achieve the characteristics of high liquid retention and high ionic conductivity.
[0070] The heating rate of calcination is 1-10°C / min, such as 1°C / min, 3°C / min, 5°C / min, 7°C / min, 10°C / min, etc. Any value between 1-10°C / min. However, it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0071] The calcination temperature is 500-1200° C., for example, 500° C., 600° C., 700° C., 800° C., 900° C., 1000° C., 1100° C., 1200° C., etc., any value between 500-1200° C. However, it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0072] The calcination time is 0.5-10 h, for example, any value between 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h and 10 h, etc. However, it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0073] Under the combined influence of a specific heating rate and calcination temperature, the first metal reactant of the embodiment of the present invention obtains porous powder particles (such as alumina powder) with a porous structure and controllable pore size and pore volume.
[0074] S2, forming a modified porous powder;
[0075] The embodiment of the present invention adopts a secondary hydrothermal reaction to obtain a modified porous powder for preparing a battery separator.
[0076] The porous powder particles are mixed with the modification aid for hydrothermal reaction. Specifically, the porous powder particles are dissolved in a solvent and the modification aid is added. The addition of the modification aid enables it to have the function of adsorbing manganese ions and maintain the porous characteristics of the material. At the same time, by including pores, the porous powder particles can have a larger specific surface area and provide the ability to substantially adsorb manganese ions to the porous coating.
[0077] The temperature of the hydrothermal reaction is 90-170° C., for example, 90° C., 100° C., 110° C., 120° C., 130° C., 140° C., 150° C., 160° C., 170° C., etc., any value between 90-170° C. However, it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0078] The time of the hydrothermal reaction is 4-48 hours, for example, any value between 4-48 hours such as 4h, 5h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h and 48h, etc. However, it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0079] In a third aspect, the present invention provides a battery separator, which includes a film substrate and a coating disposed on the film substrate, wherein the coating is prepared by the modified porous powder described in the aforementioned embodiment.
[0080] It should be noted that the specific method of using the modified porous powder in the diaphragm provided in the embodiment of the present invention is a conventional technical means; those skilled in the art can adaptively select and adjust it according to actual needs.
[0081] After the modified porous powder prepared in the embodiment of the present invention is prepared into a slurry (without modifying the diaphragm slurry formula), it can be coated by conventional coating means.
[0082] Optionally, the porous modified powder prepared by the present invention can also be used in combination with other substances that can be used for diaphragms. The present invention is applicable to any solution that can be known by those skilled in the art within a reasonable range.
[0083] The adsorption rate of manganese ions dissolved from the positive electrode of the lithium manganese-based active material can be 20% to 50%. Within the above range, the precipitation of impurities including manganese on the negative electrode can be delayed or reduced.
[0084] In a fourth aspect, the present invention provides a battery, comprising the battery separator described in the aforementioned embodiment.
[0085] In summary, when the modified porous powder doped with the modification aid provided in the embodiment of the present invention is used to prepare lithium-ion battery diaphragm coating, a high-quality lithium battery diaphragm is obtained. At the same time, due to the loading of the modification aid, the diaphragm has the effect of adsorbing manganese ions, and the adsorption rate can be 20% to 50%.
[0086] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0087] Example 1
[0088] The embodiment of the present invention provides a method for preparing a modified porous alumina powder, comprising:
[0089] S1: Add 1T aluminum hydroxide, 0.1KG triquaternary ammonium, and 2.4T pure water into a hydrothermal reactor, and perform hydrothermal reaction at 200°C for 6 hours to prepare a first alumina reaction body with a particle size of 0.7μm. The crystal water content of the first alumina reaction body is 13wt%.
[0090] S2: The first alumina reactant is spray dried into powder.
[0091] S3: The powder of S3 was placed in a crucible for calcination. The heating rate was controlled at 5°C / min, the calcination temperature was controlled at 700°C, and the insulation time was 2h to obtain a porous alumina powder with a particle size of 0.7μm, a pore volume of 0.9cm3 / g, and a pore diameter of 4nm.
[0092] S4: Add 1T of porous alumina powder, 10KG of polyacrylic acid, and 2.4T of pure water into a hydrothermal reactor, and perform a hydrothermal reaction at 120°C to obtain a modified porous alumina with a modification amount of 1%.
[0093] S5: spray-drying the modified porous alumina into powder to prepare the modified porous alumina powder.
[0094] Example 2-Example 10
[0095] Examples 2-10 respectively provide a method for preparing a modified porous alumina powder, which is referred to the method for preparing a modified porous alumina powder provided in Example 1, with only some operating conditions being different. Specifically, as follows:
[0096] Example 2: The modification aid used in S3 is 20 kg of citric acid, and a modified porous alumina powder with a modification aid loading of 2 wt % is obtained. The other conditions are consistent with those in Example 1.
[0097] Example 3: The modification aid used in S3 is 30 kg of succinic acid, and a modified porous alumina powder with a modification aid loading of 3 wt % is obtained. The other conditions are consistent with those in Example 1.
[0098] Example 4: The modification aid used in S3 is 50 kg of formic acid, and the second hydrothermal reaction is carried out at 150°C for 6 hours to obtain a modified porous alumina powder with a modification aid loading of 5 wt%. The other conditions are consistent with Example 1.
[0099] Example 5: The modification aid used in S3 is 60 kg of acetic acid, and the second hydrothermal reaction is carried out at 150°C for 6 hours to obtain a modified porous alumina powder with a modification aid loading of 5.8 wt%. The other conditions are consistent with Example 1.
[0100] Example 6: The modification aid used in S3 is 70 kg of polyacrylic acid, and the second hydrothermal reaction is carried out at 150°C for 6 hours to obtain a modified porous alumina powder with a modification aid loading of 7 wt%. The other conditions are consistent with Example 1.
[0101] Example 7: The modification aid used in S3 is 80 kg of polyacrylic acid, and the second hydrothermal reaction is carried out at 150°C for 6 hours to obtain a modified porous alumina powder with a modification aid loading of 8 wt%. The other conditions are consistent with Example 1.
[0102] Example 8: The modification aid used in S3 is 90 kg of polyacrylic acid, and the second hydrothermal reaction is carried out at 150°C for 6 hours to obtain a modified porous alumina powder with a modification aid loading of 9 wt%. The other conditions are consistent with Example 1.
[0103] Example 9: The modification aid used in S3 is 100 kg of polyacrylic acid, and the second hydrothermal reaction is carried out at 150°C for 6 hours to obtain a modified porous alumina powder with a modification aid loading of 10 wt%. The other conditions are consistent with Example 1.
[0104] Example 10
[0105] The preparation method of the modified porous alumina powder provided in this embodiment refers to the preparation method of the modified porous alumina powder provided in Example 1, which is as follows:
[0106] In S1, triquaternary ammonium is replaced by trimethylammonium, and the amount of trimethylammonium added is 0.5wt% of the aluminum salt. The first hydrothermal reaction is carried out at 120°C for 48h. The chemical formula of the aluminum oxide reaction body obtained in this step is Al2O3·nH2O, wherein the value of n is 1.1. The particle size of the aluminum oxide reaction body is 0.5μm, and the crystal water content of the aluminum oxide reaction body is 17wt%.
[0107] In S2, the heating rate was 1°C / min, the calcination temperature was controlled at 500°C, and the calcination time was 10 h, resulting in a particle size of 0.5 μm and a pore volume of 0.09 cm 3 / g, porous alumina powder with a pore size of 3nm.
[0108] In S3, the second hydrothermal reaction is carried out at 90° C. for 48 h.
[0109] Embodiment 11
[0110] The preparation method of the modified porous alumina powder provided in this embodiment refers to the preparation method of the modified porous alumina powder provided in Example 1, which is as follows:
[0111] In S1, triquaternary ammonium is replaced by trimethylammonium, and the amount of trimethylammonium added is 1wt% of the aluminum salt. The first hydrothermal reaction is carried out at 240°C for 4h. The chemical formula of the aluminum oxide reactant obtained in this step is Al2O3·nH2O, wherein the value of n is 1.1. The particle size of the aluminum oxide reactant is 1μm, and the crystal water content of the aluminum oxide reactant is 17wt%.
[0112] In S2, the heating rate was 10 °C / min, the calcination temperature was controlled at 1200 °C, and the calcination time was 0.5 h, resulting in a particle size of 1 μm and a pore volume of 0.02 cm 3 / g, porous alumina with a pore size of 49nm.
[0113] In S3, the second hydrothermal reaction is carried out at 190° C. for 4 h.
[0114] Comparative Examples 1-4
[0115] Comparative Examples 1-4 provide a method for preparing a modified porous alumina powder, which is based on the method for preparing a modified porous alumina powder provided in Example 1, except that some operating conditions are different. Specifically,
[0116] Comparative Example 1: This comparative example does not use homemade porous alumina, but homemade ordinary alumina (SAO-035EL) with a modified amount of 0.1%. The other conditions are consistent with Example 1.
[0117] Comparative Example 2: In this comparative example, no modifying agent is added. The remaining preparation methods and parameters are the same as those in Example 1.
[0118] Comparative Example 3: In this comparative example, 0.8% of a modifying agent is added, and the remaining preparation methods and parameters are the same as those in Example 1.
[0119] Comparative Example 4: In this comparative example, 11% of the modification aid is added. The remaining preparation methods and parameters are the same as those in Example 1.
[0120] The modified porous alumina powder or modified alumina of Examples 1-11 and Comparative Examples 1-4 were tested, and the results are shown in Table 1. The particle size was measured using a Malvern 3000 particle size tester; the pore volume and pore size data were measured using a Mack device; the amount of modified additives was measured using a burn-off test; and the manganese ion adsorption was measured using an ICP test.
[0121] Table 1 Test results
[0122]
[0123]
[0124] According to Table 1, we can see that:
[0125] (1) The preparation method provided in the embodiment of the present invention obtains an alumina powder with a porous structure through the synergistic combination of aluminum hydroxide and a doping auxiliary agent. After the alumina powder is modified, it is used for coating a lithium ion battery diaphragm to obtain a diaphragm with a manganese ion adsorption function. The addition of the modification auxiliary agent improves the hydrophilicity of the modified alumina powder.
[0126] (2) The porous alumina powder provided in the embodiment of the present invention can load more modification aids than conventional alumina, and conventional alumina has too little loading and cannot play a role.
[0127] (3) The modified porous alumina powder provided in the embodiment of the present invention cannot play the role of adsorbing manganese ions when it is not loaded with a modification aid or the loading amount of the modification aid is less than 1%.
[0128] (4) If the loading amount of the modified auxiliary agent in the modified porous alumina powder provided in the embodiment of the present invention is higher than 10%, it will cause the diaphragm to be blocked, the air permeability value will increase sharply, and the ion transmission will be affected.
[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A modified porous powder, characterized in that: The invention comprises porous powder particles and a modification auxiliary agent containing carboxylate groups loaded on the surface of the porous powder particles. Wherein, the loading amount of the modification aid is 1-10wt%.
2. The modified porous powder according to claim 1, characterized in that: The mass ratio of the porous powder particles to the modification aid is (10:1)-(100:1); Preferably, the particle size of the modified porous powder is 0.1-2 μm.
3. The modified porous powder according to claim 1, characterized in that: The porous powder particles are selected from any one of porous silica particles, porous titanium dioxide particles, porous zirconium oxide particles and porous aluminum oxide particles; preferably porous aluminum oxide particles; Preferably, the pore volume of the porous powder particles is 0.01 to 0.1 cm 3 / g; Preferably, the pore size of the porous powder particles is 3 to 50 nm; Preferably, the particle size of the porous powder particles is 0.1-2 μm; Preferably, the modification aid is selected from raw materials containing carboxylate groups and being easily soluble in water; Preferably, the modification aid is selected from at least one of citric acid, succinic acid, polyacrylic acid, formic acid, acetic acid, propionic acid, butyric acid and tartaric acid.
4. A method for preparing the modified porous powder according to claim 1, characterized in that: include: The porous powder particles are mixed with the modification aid to carry out a hydrothermal reaction.
5. The preparation method according to claim 4, characterized in that: include: The conditions of the hydrothermal reaction include: temperature of 90-170° C. and time of 4 h-48 h.
6. The preparation method according to claim 4, characterized in that: The preparation steps of the porous powder particles include: performing a first hydrothermal reaction on a hydroxide to form a first metal reactant; Then, the first metal reactant is calcined to form porous powder particles.
7. The preparation method according to claim 6, characterized in that: include: Mixing the hydroxide and the doping aid to perform a first hydrothermal reaction to form a first metal reactant; Preferably, the amount of the doping aid added is 0.01-1wt% of the amount of the hydroxide added; Preferably, the doping aid is selected from ammonium substances, preferably triquaternary ammonium or trimethylammonium.
8. The preparation method according to claim 6 or 7, characterized in that: The conditions of the first hydrothermal reaction include: temperature of 120-240°C and time of 4-48h; Preferably, the particle size of the first metal reactant is 0.1-2 μm; Preferably, the crystal water content in the first metal reactant is 17-30%; Preferably, the first metal reactant is M x O y nH2O, wherein 1≤n≤2, M represents the metal in the porous powder particles, x is 1-2, and y is any integer between 1-3; Preferably, the method comprises: spray drying the first metal reactant before calcining the first metal reactant; Preferably, the calcination conditions include: a temperature of 500-1200° C., a time of 0.5-10 h, and a calcination heating rate of 1-10° C. / min.
9. A battery separator, characterized in that: The invention comprises a film substrate and a coating arranged on the film substrate, wherein the coating is prepared by the modified porous powder according to claim 1.
10. A battery, characterized in that: It comprises the battery separator according to claim 9.
Citation Information
Patent Citations
Separator for electrochemical device and electrochemical device comprising same
CN117981159A